Enhancing Hepatitis B case finding through tech-enhanced community pharmacy: Results from a trial program in Vietnam - Khue Nguyen Y Ha; Sinit Mehtsun; Boon-Leong Neo; Tuan Minh Nguyen; Tien Ho; Hang Viet Dao; Josselyn Neukom (PLOS Global Public Health, 2026)
Hepatitis B virus (HBV) remains a major public health challenge in Vietnam. Barriers include limited awareness and access to screening as well as out-of-pocket diagnosis and treatment costs. Point-of-care rapid diagnostic tests (RDTs) offer an opportunity to expand screening and linkages to diagnosis and care. This intervention assessed technology-enhanced community pharmacies ability to provide HBV screening and find cases in Vietnam using digital monitoring and cross-sectional digital survey data. Between February 2024 and March 2025, SwipeRx partnered with the Vietnamese Pharmaceutical Association and the commercial supplier of Determine HBsAg-RDT to implement a trial program including digital campaigns, accredited digital training, in-pharmacy and mobile coaching, and supplier linkages. Monitoring and cross-sectional digital survey data were used to assess changes in HBV knowledge and practices at the pharmacy. Among 917 pharmacists who completed the accredited online training, 117 pharmacies with at least 1 trained pharmacist received coaching and procured 5,900 HBsAg-RDTs, with 48% placing repeat orders. During the same six-month period, 84% (98/117) of pharmacies identified 270 pharmacy clients who tested positive out of 2,840 unique clients screened using HBsAg-RDT prior to referral to a nearby health facility for confirmatory HBV diagnosis. Pharmacists who completed the digital training and were engaged with digital campaigns and coaching were 2.83 times more likely to stock HBsAg-RDT and reported significantly higher HBV-related knowledge and confidence compared to non-engaged pharmacists. This research demonstrates how technology-enabled training and pharmacy engagement can facilitate community access to new health products and services, including HBV screening. Optimizing test packaging, pricing, and pharmacy client demand may further expand access to and uptake of HBV screening through community pharmacies in future.